Innovative Wind Turbine (Texas Journal of Multidisciplinary Studies, 2022)
The capabilities available in the innovative wind turbine include a half-cylinder that adjusts the direction of rotation of the vertical wind turbine to the rotating impeller. The function of the half-cylinder is to direct the acting wind to the shoulders of the wings, which rotate in the direction of the wind. The halfcylinder is mounted on the wind turbine stand so that it can rotate completely, and the wind turbine is attached to the rear. The wind roller function adjusts the rotating blades inside the half-cylinder to the wind direction